#### Answer

$(x+10)(x-10)$

#### Work Step by Step

As $(a^{2}-b^{2})=(a+b)(a-b)$, we obtain:
$x^{2}-100=x^{2}-10^{2}=(x+10)(x-10)$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

$(x+10)(x-10)$

As $(a^{2}-b^{2})=(a+b)(a-b)$, we obtain:
$x^{2}-100=x^{2}-10^{2}=(x+10)(x-10)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.